Impact of Organisational Innovation on Sustainable Competitive Advantage of Manufacturing Firms in Lagos State, Nigeria - Abdul-Hameed Adeola SULAIMON; Chinenye Anthonia ONYEMAOBI; Christopher Idemudia EBEGBETALE; Taofeek Olalekan GBADAMOSI; Oladimeji Charles FAJIMOLU (Management and Economics Review)
The increased level of competition in the current business climate required the implementation of processes and systems to guarantee a sustainable organisational competitive advantage for the benefit of stakeholders. This research evaluates the association between product innovation and manufacturing firms’ sustainable competitive advantage, determine the effect of process innovation on manufacturing firms’ sustainable competitive advantage, examine the influence of administrative innovation on manufacturing firms’ sustainable competitive advantage and ascertain the joint relationship between product, process, and administrative innovation on manufacturing firms’ sustainable competitive advantage. Descriptive research design was adopted and a sample size of 131 manufacturing firms was used for the analysis. Data were collected using a questionnaire and analysed using regression analysis with the aid of SPSS Version 25. The findings showed that product innovation (β = .524, p < .005) process innovation (β = .417, p < .005) and administrative innovation (β = .488, p < .005) significantly influenced firm sustainable competitive advantage, individually and jointly. The research concludes that manufacturing organisations should prioritise innovation in their strategic plans. This study suggests ongoing product improvement through process and administrative adjustments and a culture of innovation and experimentation to find new sources of competitive advantage and create sustainable value.